Neuroinflammation Screening in Immunotherapy Trials against Alzheimer's Disease - Andreasen, Niels (SAGE-Hindawi Access to Research, 2010)
Due to side effects in the form of meningoencephalitis in the interrupted phase II AN1792 trial of active antiamyloid β(Aβ) immunization against Alzheimer's disease (AD), there has been concern that anti-Aβ immunization may cause destructive neuroinflammation. Here, we report on two patients fulfilling clinical AD criteria who were diagnosed with Lyme neuroborreliosis during screening before inclusion in anti-Aβ immunotherapy trials. The two cases illustrate the necessity of careful biochemical screening for neuroinflammatory/neuroinfectious conditions before an AD diagnosis is made and before clinical AD patients are included in trials of therapy that could impact the immune system. Should the two cases have been included and deteriorated, additional investigations might have led to the erroneous conclusion that therapy-induced meningoencephalitis had occurred.